Nas sombras do grupo galpão : compreendendo o organizing e sensemaking em um grupo de teatro - Possas, Miriam de Castro (2015)
In recent decades emerge in organizational studies a new perspective to Organizational Analysis. In this approach, Karl Weick highlights the importance of studying the processes instead of the organizational structures, and to understand the organization not as a noun but as a verb \"organizing\". So, in an attempt to spread this view for organizations, this dissertation analyzes a belo-horizontino theater group, Grupo Galpão, in order to understand it as a result of its practices, its phenomena, watching for their production of meaning and a procedural perspective. Thus, the objective of this research was: To understand how Grupo Galpão is organized as a result of its practices and processes. For this, on the first stage of the research, I used documentary sources, like books, theses, dissertations, journals, newspaper clippings and footage that narrate the history of the group, as well as personal accounts of performances, rehearsals, workshops. On the second stage, I used the observation technique known as shadowing, for 35 days, totaling 185 hours. During that time, I accompanied the group in its rehearsals, meetings, presentations, travels and administrative activities. Also, I accompanied the group on a trip to Jacareí, including the trip to the city, hosting and presentations. And, on the third phase, I realized 16 individual interviews with group members. Analysis of actions and events that constitute the web of social practices of Grupo Galpão, I observe that there is an attempt to formalize the processes, centralization the functions, verticalization of decisions and expansion of the group. However, the organizing practices makes the organization is always changing, so, I analyzed four dichotomies present in constant organization of Grupo Galpão practices: Informality X Formality, Fragmentation X Centralization, Horizontality X Verticality, Collection X Expansion. The production of meaning and its processes are, closely related to how they organize, therefore, to organize try, together, assign meaning to their actions, generating a cycle. In other words, the practice directs the creation of meaning, that, consequently, guide the next steps. In addition, I identified three cases of sensemaking: hiring an executive manager, conquest of a new space and a creation of a new show: Pocket. And, I related the absence of rules with oppression, neglect and inequality.